Environmental and Health Impacts Resulting From Burning Solid Waste Near Residential Areas in Diyala Governorate, Iraq: Dampak Lingkungan dan Kesehatan Akibat Pembakaran Limbah Padat di Dekat Kawasan Pemukiman di Kegubernuran Diyala, Irak - Abdulwahab Abdulrazaq Jbara (Academia Open, 2024)
General Background: Rapid development, population growth, and improper disposal of municipal solid waste are prevalent issues in developing countries, leading to significant environmental and health challenges. Specific Background: In Iraq’s Diyala Governorate, the absence of integrated waste management exacerbates pollution through waste burning and heavy metal contamination, posing risks to nearby residential areas. Knowledge Gap: While previous studies have addressed waste management in developing countries, there is limited research on how local waste disposal practices impact air, soil, and water quality in specific areas of Diyala. Aims: This study evaluates the air quality and levels of heavy metals in soil and water near five landfill sites in Diyala Governorate: Kanaan, Al-Khalis, Baladruz, Khanaqin, and Hamrin, aiming to assess the pollution levels and the potential health risks to nearby communities. Results: The findings reveal significant differences across the sites, with the highest pollutant concentrations in Kanaan for air (40±445.8), soil (22.18±35.64), and water (3.037±3.146), while Hamrin recorded the lowest concentrations. All sites demonstrated statistically significant differences (P < 0.05). Novelty: This study provides the first comprehensive analysis of the environmental impact of waste disposal practices in Diyala, linking pollutant concentrations with specific landfill sites. Implications: The results underscore the need for improved waste management strategies, including monitoring, waste sorting, and recycling initiatives, to mitigate the negative effects on public health and the environment, particularly in areas near waste dumps. Highlights: Pollution levels vary significantly across Diyala's landfill sites. Kanaan site has the highest air, soil, and water contamination. Better waste management is needed to reduce environmental and health risks. Keywords: Municipal waste, environmental pollution, heavy metals, Diyala Governorate, landfill impact